PENDIDIKAN DAN KETERAMPILAN HUKUM BAGI TENAGA KERJA MIGRAN DI INDONESIA SEBAGAI UPAYA MELINDUNGI DIRI SENDIRI DALAM KONFLIK KETENAGA KERJAAN INDONESIA - Wahyudi, Arief; Fibriasari, Hesti; Syahputra, Ricky Andi; Anastasya Sihaloho, Oksari; Riyanto, R Benny; Prajanti, Sucihatiningsih Dian Wisika; Hastihamira, Mira (Batara Wisnu : Indonesian Journal of Community Services, 2024)
This research aims to generally address the continuously increasing number of Indonesian migrant workers in Malaysia. Illegal Indonesian migrant workers in Malaysia are vulnerable to exploitation, abuse, and legal violations. The lack of understanding of immigration laws and legal protections can make them more vulnerable to adverse situations. Therefore, basic legal education and skills for illegal immigrant workers become important to enhance protection and social integration for these illegal migrant workers. The profile of the area where the service will take place is the Consulate General of the Republic of Indonesia (KBRI) in Malaysia. The Indonesian Consulate General (KBRI) is located at No.46, Jl. Taat, Off Jalan Tun Abdul Razak 80100 Johor Bahru, Johor Malaysia. The goal of the community partnership program for illegal Indonesian migrant workers in Malaysia is to provide basic knowledge about employment, including rights and obligations as citizens, so that they can anticipate potential conflicts arising from their illegal status. The stages of legal education and skills begin with socializing Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers, providing soft skills training in language proficiency, and skills in the field of science